2008
DOI: 10.1016/j.ejca.2008.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human VEGF165b protein is an effective anti-cancer agent in mice

Abstract: Tumour growth is dependent on angiogenesis, the key mediator of which is vascular endothelial growth factor-A (VEGF-A). VEGF-A exists as two families of alternatively spliced isoforms - pro-angiogenic VEGF(xxx) generated by proximal, and anti-angiogenic VEGF(xxx)b by distal splicing of exon 8. VEGF(165)b inhibits angiogenesis and is downregulated in tumours. Here, we show for the first time that administration of recombinant human VEGF(165)b inhibits colon carcinoma tumour growth and tumour vessel density in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 15 publications
0
73
1
2
Order By: Relevance
“…13,19,45,46 Thus, parenterally administered rhVEGF 165 b (intraperitoneal and subcutaneous) halts colonic carcinoma tumor growth in nude mice. 17 We have also shown that transgenic mice overexpressing VEGF 165 b in mammary tissue have inhibited physiologic angiogenesis. 15 VEGF 165 b inhibits both angiogenesis and vasodilatation through inhibition of VEGF 165 -mediated full activation of VEGF-R2.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…13,19,45,46 Thus, parenterally administered rhVEGF 165 b (intraperitoneal and subcutaneous) halts colonic carcinoma tumor growth in nude mice. 17 We have also shown that transgenic mice overexpressing VEGF 165 b in mammary tissue have inhibited physiologic angiogenesis. 15 VEGF 165 b inhibits both angiogenesis and vasodilatation through inhibition of VEGF 165 -mediated full activation of VEGF-R2.…”
Section: Discussionmentioning
confidence: 97%
“…Replacement of 8a by exon 8b in the VEGF xxx b family produces peptides that are antiangiogenic, inhibit permeability chronically, and reduce rather than promote tumor growth. 13, [15][16][17][18][19][20] Alternative splicing of ex- The gDNA is digested with EcoRI, and a probe made from the cDNA is used to generate the transgene. There was a single EcoRI site in the 5Ј end of the insert, so multiple insertions should generate multiple different-sized bands in the transgene.…”
mentioning
confidence: 99%
“…This twice weekly i.p. dosing regime has proven successful in the amelioration of diabetic nephropathy [21], traumatic nerve injury [16] and in vivo tumour models [22]. .…”
Section: Experimental Animals and Proceduresmentioning
confidence: 99%
“…21 We therefore assessed the efficacy of systemic rh VEGF-A 165 b injections in STZ-induced diabetes in DBA2J mice before and after the onset of diabetic nephropathy ( Figure 4A). After 2 weeks of consistent hyperglycemia, lowdose 0.04mg/g rh VEGF-A 165 b injections were initiated and continued until an approved study endpoint occurred (significant weight loss).…”
Section: Systemic Injections Of Vegf-a 165 B Protect Against Diabeticmentioning
confidence: 99%